(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The author in the paper present a review and description of legal regulations regarding position of the city officials and civil servants in the Osijek city administration in the period 1881-1918. Problems of the civil servants system in the city community of Osijek will be seen in relation to three groups of questions: the classification of civil servants, the payment system and the progress system. In the introduction the author gives legal definition and meaning of the terms official and civil servant. In the central part of the paper the author gives an overview and analysis normative regulation of the position of city officials and servants, ie status and wages. Legislation regulations that regulated the status and position of officials and civil servants, especially the rulebook from 1918, started a process that resulted in a growing need for expertise, in addition to experience. The author concludes that the beginnings of professional management can already be noted in the research period as people with appropriate qualifications have been employed and that accomplished organizational solutions meant progress compared to previous organization.